Sulfur/reduced graphite oxide and dual-anion solid polymer‒electrolyte integrated structure for high-loading practical all-solid-state lithium–sulfur batteries - Eun Mi Kim; Jinseok Han; Guk-Tae Kim; Huan Li; Meng Yang Cui; Ganghwan Park; Dong-Ho Baek; Bo Jin; Sang Mun Jeong; Jae-Kwang Kim (NPG Asia Materials)
Abstract The demand for high-capacity batteries with long cycle life and safety has been increasing owing to the expanding mid-to-large battery market. Li–S batteries are suitable energy-storage devices because of their reversibility, high theoretical capacity, and inexpensive construction materials. However, their performance is limited by various factors, including the shuttle effect and dendrite growth at the anode. Here, an integrated electrode for use in all-solid-state (ASS) Li–S batteries was formed via hot pressing. In detail, S particles dispersed in a functionalized reduced graphite oxide (rGO) cathode with a binder-less polymer electrolyte (PE) and a dual-anion ionic liquid-containing cross-linked poly(ethylene oxide)–Li bis(fluoromethanesulfonyl)imide–N-butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl) imide-based solid polymer electrolyte (SPE, PEO–LiFSI0.1(Pyr14TFSI)0.4) were hot-pressed into an integrated electrode, which serves as both the cathode and electrolyte. The resulting S/rGO-based solid-state Li–S batteries exhibited more stable performance than Li–S batteries using liquid electrolytes did, indicating that the dual-anion SPE layer effectively suppressed dendritic Li formation and the shuttle effect with high ionic conductivity. At 0.1 C, the battery discharge capacities were 957 and 576 mAh g−1 in the first cycle and after 100 cycles, respectively. At 1 C, the reversible capacity was 590 and 417 mAh g−1 in the first cycle and after 100 cycles, respectively (capacity retention = 71%). Therefore, the proposed S/rGO/PE//LiFSI0.1(Pyr14TFSI)0.4-integrated electrodes are beneficial for ASS Li–S batteries.